Інституціональний аспект інноваційної модернізації агропромислового виробництва - Гончаренко О, ксана Володимирівна; Honcharenko, Oksana; Тимощук, Василь Васильович; Tymoshchuk, Vasyl (Дніпровський державний технічний університет, 2023)
Обґрунтовано інституціональні детермінанти інноваційної модернізації агропромислового виробництва. Встановлено, що трансформаційними особливостями вітчизняної агросфери стали: монокультурне агропромислове виробництво, його структурна деформація, посилення деградації земельних та водних ресурсів, зростання залежності агровиробників від імпорту ресурсів для виробничого процесу і скорочення чисельності сільських працівників та населення сільських громад. Аргументовано, що трансформаційні перетворення агропромислового виробництва мають бути орієнтованими на масштабні модернізаційні зміни виробничого процесу за умов відтворення родючості земель, покращення якісних характеристик харчових продуктів, розширення наявного експортного потенціалу аграрної продукції і частки конкурентоспроможної продукції. Обґрунтовано, що інституціональне забезпечення інноваційної модернізації агропромислового виробництва має супроводжуватися формуванням ефективних базисних і спеціальних інститутів та інституції, що відповідатимуть критеріям системності при їх включенні в ієрархічну структуру норм та інститутів інноваційного спрямування. Визначені стратегічні орієнтири інноваційної модернізації агропромислового виробництва: запровадження мотивів та стимулів для структурних змін аграрного виробництва, активізація розвитку малих форм господарювання, інтеграція виробничих процесів, використання конкурентних переваг. The institutional determinants of innovative modernization of agricultural production are substantiated. It is established that the transformational features domestic agricultural production are monoculture agricultural production, its structural deformation, increased degradation of land and water resources, growing dependence of agricultural producers on imported inputs for the production process, and a reduction in the number of rural workers and the population of rural communities. It is argued that transformational changes in agro-industrial production should be focused on large-scale modernization changes in the production process in terms of restoring land fertility, improving the quality characteristics of food products, expanding the existing export potential of agricultural products and the share competitive products. It is established that the threats to the recovery of agricultural production are the narrowing of the domestic consumer market; reduction of the purchasing power of the population with a decrease in its number; reduction and blocking of exports of agricultural products; rising costs of material resources and rising costs of agricultural products and food prices. It is substantiated that institutional support for the innovative modernization of agroindustrial production should be accompanied by the formation of effective basic and special institutions and institutions that meet the criteria of systematicity when they are included in the hierarchical structure of norms and institutions of innovation. It is emphasized that the institutional support for innovative modernization should implement the following key tasks: ensuring a favorable investment climate for attracting financial resources to processing enterprises and the formation of local regional structures with low capacity for processing agricultural raw materials; creating conditions for the inclusion of agricultural producers in global value chains. Institutional interventions should be aimed at stimulating the diffusion and development of product innovations; supporting and shaping organizational structures for vertical and horizontal integration; supporting and shaping organizational frameworks for vertical and horizontal integration; and restructuring forms of state support for agricultural production. The strategic guidelines for the innovative modernization of agro-industrial production are defined: introduction of motives and incentives for structural changes in agricultural production, intensification of the development of small forms of management, integration of production processes, and use of competitive advantages
Institutional aspect innovative modernization of agricultural production
Keywords: агропромислове виробництво; agro-industrial production; модернізація; modernization; інноваційний розвиток; innovative development; інституціональне забезпечення; institutional support; інститут; institution; трансформація; transformation